Meningkatkan Hasil Belajar PAKAT Melalui Model Problem Base Learning Fase D Kelas VII SMP Negeri 23 Kota Surakarta - Lukas Didik Prakoso; FX. Sugiyana; Veronica Nurhayati (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to describe the implementation of the Problem Based Learning (PBL) model in improving learning outcomes for Catholic Religious Education (PAK) among seventh-grade students in Phase D at SMP Negeri 23 Surakarta. The Classroom Action Research (CAR) method was used with two cycles to evaluate the effectiveness of PBL in enhancing student learning outcomes. The research shows an improvement in learning outcomes, covering cognitive, psychomotor, and critical reasoning affective aspects. In Cycle I, only 25% of students were categorized as proficient in the cognitive aspect, but this increased to 63% in Cycle II. Psychomotor aspects, such as journal writing and prayer formulation, also showed significant progress. In terms of affective skills, students capable of critical reasoning increased from 25% in Cycle I to 75% in Cycle II. The application of PBL also encouraged the development of soft skills like leadership, teamwork, and self-confidence. In conclusion, the PBL model enhances students' critical thinking, collaboration, and creativity while strengthening their understanding of PAK material.